Sanches, Becoming Mexican American - Ethnicity, Culture, And Identity In Chicano Los Angeles, 1900-1945 - Reeves, Kay (Teaching History: A Journal of Methods, 1996)
Becoming Mexican American explores the complex process by which Mexican immigrants and their American-born children living in Los Angeles between 1900 and 1945 were transformed from being Mexicans living in the United States to ethnically and culturally identifying themselves as Mexican Americans. Following an introduction that reviews the historiography, both sociological and historical, on cultural adaptation and ethnic identity of immigrants in general and Mexicans in particular, Sanchez divides his study into four major parts.